2018
DOI: 10.1016/j.applthermaleng.2018.08.068
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of wall thickness and hole shape variation effects on full-coverage film cooling performance for a gas turbine vane

Abstract: The effects of wall thickness and hole shape variation on a full-coverage film cooled turbine vane are investigated in a stationary and linear cascade utilizing the pressure sensitive paint technique. The varied wall thickness produces hole lengthto-diameter ratio (L/D) in a range from L/D=2 to 5, and holes tested include simple angle hole, compound angle hole, and fan-shaped hole. Five rows of holes are provided on the pressure side while three rows of holes are provided on the suction side, with six rows of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The choice of the hole exit shape is a usual problem in the study of film cooling. 15,16 In this study, we refer to the optimization method of hole shape in the film cooling and apply the method to the study of the endwall VGJs. The effect of the hole exit shape on the aerodynamic performance of the compressor cascade is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the hole exit shape is a usual problem in the study of film cooling. 15,16 In this study, we refer to the optimization method of hole shape in the film cooling and apply the method to the study of the endwall VGJs. The effect of the hole exit shape on the aerodynamic performance of the compressor cascade is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the correlations developed for flat plate configurations overestimated the film cooling effectiveness at the pressure side and the last cooling hole row of the suction side. Li et al [8] measured the film cooling effectiveness on a full-coverage film cooled turbine vane with three hole configurations: cylindrical hole, compound angle hole, and fan-shaped hole.…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing desire to achieve higher thermal efficiency while lower cooling air consumption promotes combined cooling concepts to be proposed. 1,2 Near turbine blade trailing edge (TE) region, TE slots coupling with upstream discrete film-holes and internal pedestals (as illustrated in Figure 1(a)) have been widely designed to effectively respond the challenges of severe local high temperature level. [3][4][5] Hence, the actual coolant coverage performance at cutback surface is determined by the interaction of hot mainstream, TE slot outflow and upstream pressure side (PS) film-ejection.…”
Section: Introductionmentioning
confidence: 99%